Modeling of the impact of GDP and human population on CO2 emission by using Cobb-Douglas model and particle swarm optimization - Hafizan, J.; Sukono, .; Subartini, B.; Susia, .; Supian, S.; Napitupulu, H.; Budiono, R. (2019)
High economic growth and population can cause a negative impact on the environment, one of which is the increase of CO2 emissions in the air. In the paper, modelling the impact of GDP and human population on CO2 emissions in Indonesia. In this paper the modelling is done by using Cobb-Douglas model, and for parameter estimation done with particle swarm optimization (PSO). The data used in this modeling is GDP growth and human population over the period 1967-2014.Based on the results of the analysis it can be shown that the impact of GDP and human population on CO2 emissions, significantly follow the Cobb- Douglas model. The parameter estimation using PSO yields elasticity estimators for GDP and the human population are 0.195517125 and 1.558049947, respectively. Since the sum of elasticity estimators is greater than one, this shows the characteristic proportion of the increase in GDP and human population, will increase CO2 emissions by a larger proportion.